Practice and Barriers of Breast Self-Examination Among Women in a Rural Community in South Western, Nigeria (International Journal of Studies in Nursing, 2019)
Background: Breast cancer (BC) is the most common cancer and the second cause of cancer deaths in women worldwide as well as in Nigeria .The incidence of the disease appears to be rising faster in a population groups which had hitherto enjoyed low incidence, with the peak age of breast cancer in Nigerian women being about ten years earlier than Caucasians Aim: This study investigated the practice of BSE and its possible barriers among women in a rural community in South Western area of Oyo State; Nigeria. Study design: The study utilized Participatory Action Research (PAR) design using purposive and cross sectional sampling technique for survey and 95 women for the focus group discussion. The PAR framework involves four phases: Observe, Reflect, Plan and Act. Structured questionnaire was used for phase one, and A - 3 session FGD was used for phases on Reflect and Plan. Data was analyzed using the SPSS version 21, while content analysis for FGD to identify common themes. Results: The study reveals that 75.1% had no knowledge of breast self-examination at all while only 24.9% had knowledge of what BSE, their sources of information was majorly health Professionals (47.5%), electronic media (21.4%), 76.5% did not practice BSE. Also, about 77% of the respondents expressed one form of barrier or another to BSE practice. Major barriers to the practice of BSE identified are revealed based on these themes: - „knowledge/awareness of BSE‟, „practice and appeal for intervention‟, and „misconceptions and fear of being diagnosed‟. Conclusion: More than half of the participants do not practiced BSE. Some socio demographic significantly influenced the practice of the BSE. Lack of knowledge, not having any symptoms, myths and being afraid of being diagnosed with breast cancer were the main barriers to practicing BSE. There is need to develop a continuous awareness campaign among rural women on the importance of performing BSE.